TRANSPARANSI DAN TANTANGAN AKAD MURĀBAHAH BIL WAKĀLAH: Studi Implementasi di Bank Muamalat Jakarta - zainal arifin, Muhammad; Khusnul Khotimah, Umi; Arif Khan, Dawud (Al-Maqashid: Journal of Economics and Islamic Business, 2025)
This study examines the implementation of the murābaḥah bi al-wakālah contract in car financing at Bank Muamalat Indonesia, the first Islamic bank that plays a significant role in the development of Islamic finance in the country. The research background is based on the dominance of the murābaḥah contract in the financing portfolio, as well as issues related to asset ownership and the customer’s role as wakīl, which remain subject to both normative and practical debates. The objective of this study is to provide a detailed analysis of the implementation stages of the murābaḥah bi al-wakālah contract at Bank Muamalat and to assess its compliance with DSN-MUI Fatwa No.04/DSN-MUI/IV/2000. A qualitative approach with a case study method was employed, using in-depth interviews, field observations, and document analysis. The findings reveal that Bank Muamalat’s operational procedures generally comply with Islamic legal principles, covering the stages of application, agency authorization, purchase, verification, murābaḥah contract execution, and installment monitoring. Nevertheless, two critical issues remain: insufficient documentation of asset ownership and the low level of customer understanding of their role as wakīl. These gaps may potentially shift the contract into a practice resembling conventional credit. The study concludes that strengthening ownership documentation and enhancing customer education are crucial to uphold shariah compliance. Academically, this research contributes to the literature on contemporary Islamic commercial jurisprudence, while practically it provides recommendations to improve the operational procedures of Islamic banking.